Odd duck - Castellucci, Cecil 1969- (First Second, 2013)
"Theodora is a perfectly normal duck. She may swim with a teacup balanced on her head and stay north when the rest of the ducks fly south for the winter, but there's nothing so odd about that. Chad, on the other hand, is one strange bird. Theodora quite likes him, but she can't overlook his odd habits. It's a good thing Chad has a normal friend like Theodora to set a good example for him. But who exactly is the odd duck here? Theodora may not like the answer"--Book jacket
Keywords: Individuality / Juvenile fiction; Friendship / Juvenile fiction; Ducks / Juvenile fiction; Graphic novels; Individuality / Comic books, strips, etc / Juvenile fiction; Friendship / Comic books, strips, etc / Juvenile fiction; Ducks / Comic books, strips, etc / Juvenile fiction; Freundschaft; Individualität; Comic; Jugendbuch